VSe2-reduced graphene oxide as efficient cathode material for field emission. (May 2019) - Ratha, Satyajit; Bankar, Prashant; Gangan, Abhijeet Sadashiv; More, Mahendra A.; Late, Dattatray J.; Behera, Jogendra N.; Chakraborty, Brahmananda; Rout, Chandra Sekhar
Abstract: Field emission properties of pristine VSe2 and its hybrid with reduced graphene oxide (RGO) have been investigated in detail. Promising field emission performance were noted with lower values of turn-on and threshold fields of ∼1.3 V μm −1 and 2.12 V μm −1 respectively for the VSe2 /RGO hybrid which is much more superior than that of pristine VSe2 emitter and other 2D materials. Density Functional Theory (DFT) simulations have also been performed to qualitatively support our experimental observations through demonstration of Density of States and computation of work function for pristine VSe2 and hybrid VSe2 /RGO. The lowering of work function and appearance of additional states near Fermi level from carbon p orbital of RGO is responsible for superior field emission characteristics in hybrid VSe2 /RGO compared to pristine VSe2 which supports our experimental observations. Our experimental data and theoretical insight from electronic structure simulations strongly infer that the synthesized hybrid VSe2 /RGO has the potential to be tailored as efficient and high performance cathode material in field emission based devices. Graphical abstract: Image 1 Highlights: Promising field emission performance of VSe2 /RGO hybrid. Turn-on and threshold fields of ∼1.3 V μm −1 and 2.12 V μm −1 respectively. DFT simulations qualitatively supported our experimental observations. VSe2 /RGO has the potential to be tailored as efficient and high performance cathode material.